Synthesis, characterizations, crystal structures, BSA-binding, molecular docking, and cytotoxic activities of nickel(II) and copper(II) coordination complexes with bidentate N, S-chelating ligand. Issue 10 (19th May 2019) - Noorussabah, N.; Choudhary, Mukesh; Jana, Achintya; Das, Neeladri; Mohan, B.; Ahmad, K.; Sangeeta, S.; Bharti, S.; Mishra, M. K.; Sharma, S. R.
Abstract: In the present investigation, we report the synthesis and characterization of three novel nickel(II) [Ni(L)2 ] (1 ) and copper(II) [Cu(L)2 ] (2a ) and [Cu(L)2 ] (2b ) complexes, which are made through the coordination of ( E )-1-(2-methoxybenzylidine)-4-phenylethiosemicarbazone (HL) as bidentate N, S-ligand. Several modern techniques including experimental electronic and fluorescence spectroscopy, single-crystal X-ray crystallography, molecular docking and BSA-binding are used to characterize the isolated coordination compounds. X-ray crystallography, FT-IR and UV–visible spectra agree with the observed crystal structures. The crystallographic and spectroscopic studies confirmed that these complexes display four-coordinate square-planar trans -[MN2 S2 ] coordination geometry, whose central metal(II) atom lies on the center of symmetry. Complexes1 and2a crystallized in the orthorhombic system of the space group Pbca whereas2b crystallized in the monoclinic system of P21 /c. The binding affinity of complexes towards bovine serum albumin (BSA) was determined by UV–visible and fluorescence spectrophotometric methods. The cytotoxic/antiproliferative potential of the synthesized compounds on human cell lines was also investigated by MTT assay. Abstract :